Therapeutic development to accelerate malaria control through intentional intervention layering - Lydia Braunack-Mayer; Narimane Nekkab; Josephine Malinga; Sherrie L. Kelly; Evelyn Ansah; Joerg J. Moehrle; Melissa A. Penny (Malaria Journal)
Abstract The clinical development of novel vaccines, injectable therapeutics, and oral chemoprevention drugs has the potential to deliver significant advancements in the prevention of Plasmodium falciparum malaria. These innovations could support regions in accelerating malaria control, transforming existing intervention packages by supplementing interventions with imperfect effectiveness or offering an entirely new tool. However, to layer new medical tools as part of an existing programme, malaria researchers must come to an agreement on the gaps that currently limit the effectiveness of medical interventions for moderate to low transmission settings. In this perspective, three crucial gaps that may prevent new therapeutics from being used to their fullest extent are presented. First, do burden reduction outcomes, which are typically monitored in studies of new medical products, sufficiently capture the broader goal of accelerating malaria control? Layering novel malaria products requires monitoring health outcomes that reflect the novel product’s targeted stage of the parasite life cycle, in addition to all-infection and prevalence-based outcomes. Second, what public health outcome does a novel medical prevention tool provide that existing malaria interventions cannot fully deliver? Novel medical tools should be developed not just for an incremental improvement in preventive efficacy over an existing product, but also to meet a gap in protection. Specifically, this means designing products with components that target parts of the parasite life cycle beyond the scope of existing therapeutics, and better addressing populations and settings not well covered by existing tools. Finally, when do the population-level benefits of a multi-tool prevention programme justify the individual-level outcomes from receiving multiple interventions? An individual-level perspective should be key for exploring when and how layering a novel prevention intervention can accelerate efforts towards P. falciparum malaria control.